Analisis Cemaran Logam Berat Cr (VI) Dan Isolasi Bakteri Pereduksinya Pada Limbah Cair Pewarna Batik di Kota Tasikmalaya - Hernawan, Edi; Meylani, Vita (Journal of Natural Sciences, 2024)
The location of Cigeureung, Nagarasari Village, Cipedes District, Tasikmalaya City is a prominent hub for batik production in East Priangan, where a significant amount of liquid waste from batik dye is generated. Textile dyes are integral components of the batik-making process and encompass a multitude of heavy metals that possess the potential to contaminate the environment and negatively impact groundwater nutrients. Among these heavy metals, Hexavalent Chromium (Cr (VI)) stands out as a hazardous element for environmental well-being. In addition, batik liquid waste harbors many indigenous microorganisms capable of decomposing pigments. This study sought to ascertain the concentration of heavy metals and explore methods for their degradation through the utilization of biological agents, specifically microorganisms. In this particular instance, the Neutron Activation Analysis (NAA) approach was employed to ascertain the concentration of Cr (VI) present in the textile dye, utilizing both qualitative and quantitative methodologies. Isolation is conducted to identify bacteria capable of degrading colors. This process involves isolating bacteria from liquid waste and subsequently identifying them visually and physiologically, following the guidelines outlined in the Bergeys Manual taxonomy book. The study revealed that batik liquid waste collected at various distances exhibited a Cr (VI) concentration below 0.04, thereby satisfying the criteria for environmental quality. In addition, batik liquid waste contains many genera of bacteria, including as Streptococcus, Bacillus, and Streptobacillus.